2015
DOI: 10.1016/j.jinteco.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Are the benefits of export support durable? Evidence from Tunisia

Abstract: published by Elsevier. It is posted here by agreement between them. Changes resulting from the publishing process-such as editing, corrections, structural formatting, and other quality control mechanisms-may not be reflected in this version of the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 39 publications
1
51
1
Order By: Relevance
“…Although prior studies have recognized EPPs' importance in firm's exports, empirical results are inconsistent. While some research indicates the adoption of EPPs has a direct and positive impact on export outcome (Francis, Collins-Dodd 2004;Sousa, Bradley 2009), or through the intervening effects of factors such as firms' capabilities, resources, and strategies (Shamsuddoha, Ali 2006;Shamsuddoha et al 2009), other research demonstrates non-significant impact of EPPs (Ayob, Freixanet 2014;Cadot et al 2015). Furthermore, some research suggests a more complex association between EPPs and export performance.…”
Section: Epps and Export Performancementioning
confidence: 99%
“…Although prior studies have recognized EPPs' importance in firm's exports, empirical results are inconsistent. While some research indicates the adoption of EPPs has a direct and positive impact on export outcome (Francis, Collins-Dodd 2004;Sousa, Bradley 2009), or through the intervening effects of factors such as firms' capabilities, resources, and strategies (Shamsuddoha, Ali 2006;Shamsuddoha et al 2009), other research demonstrates non-significant impact of EPPs (Ayob, Freixanet 2014;Cadot et al 2015). Furthermore, some research suggests a more complex association between EPPs and export performance.…”
Section: Epps and Export Performancementioning
confidence: 99%
“…The impact seems stronger along the extensive margin than along the intensive one (Alvarez and Crespi, 2000;Volpe and Carballo, 2008). Cadot et al (2012) evaluated the effects of the FAMEX export promotion programme in Tunisia on the performance of beneficiary firms. While much of the literature assesses only the short-term impact of such programmes, their paper also considers the longer-term impact.…”
Section: Early Results: Does Export Promotion Make a Difference?mentioning
confidence: 99%
“…However, in a subsequent study it was found that the effects were not sustained over time, an issue that the authors highlighted as commonly overlooked in the literature (Cadot et al 2012). The authors of the follow-up study even mention that these types of reforms have not been explored in the long term, questioning the sustainability of what in the short-term was found to be "successful" (Cadot et al 2012). Ravallion (2009) warns that the assessment of short-term impacts is common in impact evaluation, generating a "myopia bias" that can lead not only to erroneous conclusions but also to decisions to scale-up policies and programs without knowing the underlying factors of impact that can lead to negative spillovers.…”
Section: Understanding Impact Trajectoriesmentioning
confidence: 96%
“…For example, a study that evaluated the impact of an export promotion-matching grant for small and medium-sized enterprises (SMEs) in Tunisia found that in the short term, beneficiary firms showed higher export growth and export diversification than those of the control group. However, in a subsequent study it was found that the effects were not sustained over time, an issue that the authors highlighted as commonly overlooked in the literature (Cadot et al 2012). The authors of the follow-up study even mention that these types of reforms have not been explored in the long term, questioning the sustainability of what in the short-term was found to be "successful" (Cadot et al 2012).…”
Section: Understanding Impact Trajectoriesmentioning
confidence: 99%